2013
DOI: 10.5665/sleep.2708
|View full text |Cite
|
Sign up to set email alerts
|

Adenotonsillectomy in Obese Children with Obstructive Sleep Apnea Syndrome: Magnetic Resonance Imaging Findings and Considerations

Abstract: This is the first report to quantify volumetric changes in the upper airway in obese children with OSAS after adenotonsillectomy showing significant residual adenoid tissue and an increase in the volume of the tongue and soft palate. These findings could explain the low success rate of AT reported in obese children with OSAS and are important considerations for clinicians treating these children.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
60
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 58 publications
(65 citation statements)
references
References 42 publications
3
60
0
2
Order By: Relevance
“…38,39 Correspondingly, our study confirmed the higher failure rate in obese children during the followup evaluation. The rate of obesity in our cohort was 16.5%, which is lower than some related US studies, but is similar to others.…”
Section: Discussionsupporting
confidence: 77%
“…38,39 Correspondingly, our study confirmed the higher failure rate in obese children during the followup evaluation. The rate of obesity in our cohort was 16.5%, which is lower than some related US studies, but is similar to others.…”
Section: Discussionsupporting
confidence: 77%
“…Further, we have previously shown by volumetric analysis that there is significant residual adenoid tissue following AT in obese patients that may be contributing to residual OSA in this population. 29 A recent prospective study by Thongyam et al examined the current AAP and AAO-HNS guidelines for predicting complications following AT in a large pediatric population. 12 The AAP admission criteria were found to be more significantly predictive of respiratory complications than the AAO-HNS criteria.…”
Section: Discussionmentioning
confidence: 99%
“…Drug-induced sleep endoscopy in children with persistent SDB may demonstrate laryngomalacia, adenoidal tissue regrowth, tongue base obstruction and pharyngeal collapse (class III and IV) [69,[263][264][265]. MRI of the upper airway may reveal residual adenoid tissue in obese children with persistent OSAS following adenotonsillectomy (class IV) [266]. Regrowth of adenoidal tissue, glossoptosis, hypopharyngeal collapse, soft palate collapse and hypertrophic lingual tonsil are abnormalities that may be identified by cine MRI in children with Down syndrome and persistent SDB after adenotonsillectomy (class IV) [267,268].…”
Section: Literature Reviewmentioning
confidence: 99%